how are you today by the Manus Recording Project Collective - James EK Parker; Joel Stern (Law Text Culture, 2020)
This essay is about how are you today, an artwork produced by six men then detained on Manus Island, along with their collaborators in Melbourne (together, the Manus Recording Project Collective). The work was commissioned in 2018 for an exhibition called Eavesdropping at the Ian Potter Museum of Art, at the University of Melbourne, the largest University-based museum in Australia. Each day for the fourteen weeks of the show, one of the men on Manus made a sound recording and sent it ‘onshore’ for swift upload to the gallery. By the exhibition’s end, there were eighty-four recordings in total, each ten minutes long. The result is an archive of fourteen hours—too large and diverse to synthesise, yet only a tiny fraction of the men’s indefinite internment. In this essay we introduce how are you today along with a series of reflections on it, including by two of the artists. We see our task as twofold. First, to document the work’s conception, production, and key realisations, both for the record and to spare the pieces that follow the trouble. Second, to offer a curatorial perspective in the process, since we were the ones who commissioned how are you today at the end of 2017.